Differences in bisphenol A and estrogen levels in the plasma and seminal plasma of men with different degrees of infertility - Vitku, J; Sosvorova, L; Chlupacova, T; Hampl, R; Hill, M; Sobotka, V; Heracek, J; Bicikova, M; Starka, L (Physiological research, 2015)
The general population is potentially exposed to many chemicals that can affect the endocrine system. These substances are called endocrine disruptors (EDs), and among them bisphenol A (BPA) is one of the most widely used and well studied. Nonetheless, there are still no data on simultaneous measurements of various EDs along with steroids directly in the seminal fluid, where deleterious effects of EDs on spermatogenesis and steroidogenesis are assumed. We determined levels of BPA and 3 estrogens using LC-MS/MS in the plasma and seminal plasma of 174 men with different degrees of infertility. These men were divided according their spermiogram values into 4 groups: (1) healthy men, and (2) slightly, (3) moderate, and (4) severely infertile men. Estradiol levels differed across the groups and body fluids. Slightly infertile men have significantly higher BPA plasma and seminal plasma levels in comparison with healthy men (p<0.05 and p<0.01, respectively). Furthermore, seminal BPA, but not plasma BPA, was negatively associated with sperm concentration and total sperm count (-0.27; p<0.001 and -0.24; p<0.01, respectively). These findings point to the importance of seminal plasma in BPA research. Overall, a disruption of estrogen metabolism was observed together with a weak but significant impact of BPA on sperm count and concentration.
Keywords: Male; biologické markery; Biomarkers; Infertility, Male; estrogeny; Adult; dospělí; mužské pohlaví; fenoly; benzhydrylové sloučeniny; sperma; Semen; počet spermií; lidé; Humans; Sperm Count; Benzhydryl Compounds; Phenols; Estrogens; mužská infertilita